Heteroatoms Synergistic Anchoring Vacancies in Phosphorus-Doped CoSe2 Enable Ultrahigh Activity and Stability in Li–S Batteries - Xiaoya Zhou; Wei Mao; Chengwei Ye; Qi Liang; Peng Wang; Xuebin Wang; Shaochun Tang (Nano-Micro Letters, 2025)
Highlights A volcano-type relationship between catalytic activity and vacancy concentration is revealed based on systematic investigation on selenium-vacancy-rich CoSe2. A novel “heteroatoms synergistic anchoring vacancies” tactic is firstly proposed to achieve P-doped CoSe2 with remained rich selenium vacancies (P-CS-Vo-0.5). It has been demonstrated that P doping lowers Se vacancy surface energy and effectively “pins” active sites, markedly suppressing dynamic migration of vacancies.